The Memory of the Archive: The International Tracing Service and the Construction of the Past as History. Issue 2 (4th May 2017) - Stone, Dan
ABSTRACT: This article examines the archives of the International Tracing Service (ITS) in light of recent debates concerning the implication of the digitization of archives for historical research. After a brief survey of the ITS's history, it argues that although digitization brings in its wake certain problems for historical research – in particular the loss of serendipity and a thorough grounding in the culture of place – the ITS to some extent resists these difficulties. This is a result both of the transnational nature of the ITS's vast documentary holdings and the fact that the ITS's digital environment does not currently allow for fine-grained research of the sort that allows researchers to overlook the wider context. The article argues that recent 'rational constructivist' approaches in theory of history provide fruitful ways for making sense of the categories that are to be found in the ITS archives. It then goes on, through the use of as-yet non-digitized documents from ITS pertaining to Romanian Roma and Czech Mischlinge, to show that the ITS's holdings offer great potential for writing a social history of the Holocaust, one that is sensitive to place and to the experience of the victims, even if that research often needs to make use of perpetrator documents. The aim of using non-digitized material is to show that as these documents are digitized, they lose none of their power to refocus the history of the Holocaust.